2021
DOI: 10.3390/cancers13133347
|View full text |Cite
|
Sign up to set email alerts
|

The mir-423-5p/MMP-2 Axis Regulates the Nerve Growth Factor-Induced Promotion of Chondrosarcoma Metastasis

Abstract: A chondrosarcoma is a common tumor of the soft tissue and bone that has a high propensity to metastasize to distant organs. Nerve growth factor (NGF) is capable of promoting the progression and metastasis of several different types of tumors although the effects of NGF in a chondrosarcoma are not confirmed. Here, we found that the levels of NGF and matrix metalloproteinase-2 (MMP-2) correlated with the tumor stage in patients with a chondrosarcoma. NGF facilitated the MMP-2-dependent cellular migration in huma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…In our previous experiments, we used an established orthotopic mouse model of chondrosarcoma lung metastasis to examine the stimulatory effects of NGF in metastatic chondrosarcoma [ 28 ], which confirmed that NGF promotes chondrosarcoma metastasis in mouse lungs by stimulating MMP-2 expression [ 24 ]. In this study, NGF overexpression in JJ012 cells (JJ012/NGF) promoted high levels of both NGF and LOX protein, which significantly increased the migratory ability of JJ012 cells (Fig.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…In our previous experiments, we used an established orthotopic mouse model of chondrosarcoma lung metastasis to examine the stimulatory effects of NGF in metastatic chondrosarcoma [ 28 ], which confirmed that NGF promotes chondrosarcoma metastasis in mouse lungs by stimulating MMP-2 expression [ 24 ]. In this study, NGF overexpression in JJ012 cells (JJ012/NGF) promoted high levels of both NGF and LOX protein, which significantly increased the migratory ability of JJ012 cells (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…In previous IHC tissue array investigations, we have documented higher levels of NGF and MMP-2 expression in patients with higher-grade chondrosarcoma than in those with lower-grade disease [ 24 ]. We also observed in that study a positive significant correlation between MMP-2 and NGF staining intensities of human chondrosarcoma tissue, indicating an association between the levels of these proteins and the progression of chondrosarcoma disease [ 24 ]. In this study, we investigated LOX expression in patients with chondrosarcoma.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, femur, humerus, and pelvis are also the most frequent sites of dedifferentiated chondrosarcomas, which comprise chondroid and non-chondroid parts often looking like fibroblastic or osteoblastic tissue, indicating two types of mesenchymal differentiation in one tumor [28,29]. Moreover, chondrosarcoma has a high propensity to metastasize to distant organs, especially lungs [30].…”
Section: Chondrosarcomamentioning
confidence: 99%
“…Mouse tumor tissues were rehydrated and treated with primary anti-VEGF-C or LYVE-1 antibodies, then incubated with biotin-labeled secondary antibody. The slides were treated with the ABC Kit (Vector Laboratories, Burlingame, CA, USA) according to a previous protocol [30], and then photographed using the microscope. Intra-tumoral lymph vessels were defined as LYVE-1-positive (LYVE-1 + ) vessels that were in close contact with tumor cells or located in the desmoplastic stroma.…”
Section: Immunohistochemistry (Ihc) Stainingmentioning
confidence: 99%